GREEN ACCOUNTING PRACTICES AND FIRM VALUE: EVIDENCE FROM INDONESIA’S OIL, GAS, AND COAL SUBSECTOR INDUSTRY - Esa Panganti Wideretno (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effects of green accounting, environmental performance, and firm size on firm value in oil, gas, and coal subsectors listed on the Indonesia Stock Exchange from 2019 to 2023. Using a quantitative positivist approach, the research employs secondary data drawn from annual reports, sustainability reports, and PROPER ratings, analyzed through multiple linear regression. The findings indicate that green accounting positively and significantly enhances firm value by strengthening investor confidence through clearer disclosure of environmental costs. Environmental performance shows no significant effect, likely due to inconsistent voluntary reporting practices across firms. Firm size has a negative and significant influence, suggesting structural inefficiencies among larger companies. Overall, these variables explain 16.8 percent of the variation in firm value, underscoring the importance of sustainability-based accounting and efficient management in environmentally sensitive extractive industries in Indonesia today, and strengthening long-term market confidence.